The information systems integration plan: for satellite remote sensing subsystems - Abdul Molok , Nurul Nuha (VDM Verlag Dr. Muller, 2010)
Systems integration has been given a broad array of meanings and there is no uniformly acknowledged definition for it. Thus, this book unravels the essence of systems integration describing its historic review, characteristics, challenges, and applicable tools. It also introduces an Information Systems Integration (ISI) framework to integrate existing application systems that enables data sharing in organizations. The author takes us through a journey to actualize the ISI plan by implementing it on a chosen organization and developing system prototype for its viability. Defying the traditional system development and introducing the sophisticated remote sensing technologies, this book is a must-read! (This book is based on the thesis for Master's Degree in Computer Science with specialization in Information Systems, Universiti Malaya, Kuala Lumpur, Malaysia)